Walter Pater et le paradoxe de l’idéal grec incarné par la sculpture - Anne-Florence Gillard-Estrada (Cahiers Victoriens et Edouardiens)
Walter Pater, from his essay « Winckelmann » (1867) onwards, asserted that Greece was the quintessence of culture (echoing here Matthew Arnold’s theories) as well as a model to be imitated. Pater, who was strongly influenced by the aesthetic writings of Hegel and Winckelmann, considered that the Greeks were the paragons of an ideal of unity and harmony that modern man had lost ; he also took up the prevalent topos of Greece as the youth of humanity. Greek sculpture embodies this ideal of perfection : the perfection of form, since the sensuous material and the mind combine in those representations of man seen in all his beauty. Moreover, sculpture embodies the happy subjectivity of ephebes characterised by purity, innocence and simplicity, whereas modern man is divided. However, this Greek ideal is wrought by tensions and ambivalences. The art critic’s desiring gaze lingers on the whiteness of this Greek sculpted being. Pater thus weaves an aesthetic and erotic discourse focusing on the image of the male nude. Besides, he constantly deconstructs the ideal of perfection which he had at first glorified : he no longer believes that the answer to the problems of his culture consists in turning back to this serene Greek ideal best embodied in sculpture. According to him, these statues reflect a subjectivity which is in fact impossible to regain, because it is limited, impassive and even « insipid » for it is precisely devoid of the consciousness of sin. He finally appeals to the « romantic » experience, which he finds much richer because more troubled and more complex, symbolised by those « maladies of the soul » reflected in the Mona Lisa portrait. Most of Walter Pater’s writings indeed show that he wavered between the bright ideal of the Apollinian and the destructive impulses of the Dionysiac.